Effective radium-226 concentration in meteorites. (1st July 2017) - Girault, Frédéric; Perrier, Frédéric; Moreira, Manuel; Zanda, Brigitte; Rochette, Pierre; Teitler, Yoram
Abstract: The analysis of noble gases in meteorites provides constraints on the early solar system and the pre-solar nebula. This requires a better characterization and understanding of the capture, production, and release of noble gases in meteorites. The knowledge of transfer properties of noble gases for each individual meteorite could benefit from using radon-222, radioactive daughter of radium-226. The radon-222 emanating power is commonly quantified by the effective radium-226 concentration ( EC Ra ), the product of the bulk radium-226 concentration and of the emanation coefficient E, which represents the probability of one decaying radium-226 to inject one radon-222 into the free porous network. Owing to a non-destructive, high-sensitivity accumulation method based on long photomultiplier counting sessions, we are now able to measure EC Ra of meteorite samples, which usually have mass smaller than 15 g and EC Ra < 0.5 Bq kg −1 . We report here the results obtained from 41 different meteorites, based on 129 measurements on 70 samples using two variants of our method, showing satisfactory repeatability and a detection limit below 10 −2 Bq kg −1 for a sample mass of 1 g. While two meteorites remain below detection level, we obtain for 39 meteorites heterogeneous EC Ra values with mean (min–max range) of ca. 0.1 (0.018–1.30) Bq kg −1 . Carbonaceous chondrites exhibit the largest EC Ra values and eucrites the smallest. Such values are smaller than typical values from most terrestrial rocks, but comparable with those from Archean rocks (mean of ca. 0.18 Bq kg −1 ), an end-member of terrestrial rocks. Using uranium concentration from the literature, E is inferred from EC Ra for all the meteorite samples. Values of E for meteorites (mean 40 ± 4%) are higher than E values for Archean rocks and reported values for lunar and Martian soils. Exceptionally large E values likely suggest that the 238 U- 226 Ra pair would not be at equilibrium in most meteorites and that uranium and/or radium are most likely not uniformly distributed. EC Ra of meteorites is correlated with E and seems to mainly reflect the gas permeability of the meteorite, which could be one important property, preserved in the meteorite, of its parent body, characterizing its history in space, possibly modified by alteration, shock metamorphism, and eventually weathering on Earth. Larger radon emanation values are associated with larger concentrations of the heaviest noble gases (argon, krypton, xenon), and larger 20 Ne/ 22 Ne and 36 Ar/ 38 Ar ratios, suggesting Earth's atmosphere contamination or solar wind implantation, and probably a similar carrier phase such as Q phase. An unclear correlation is observed with 40 Ar, which may rule out a purely radiogenic effect on radon emanation. Thus, larger radon emanation suggests a larger capacity of collecting solar and terrestrial gases, which should imply higher loss of gases generated in the meteorite and larger dispersion of Pb/U ratios for age determination. This study provides the first quantification of natural radon-222 loss from meteorites and opens promising perspectives to quantify the relationship between pore space connectivity and the transfer properties for noble gases in meteorites and other extraterrestrial bodies.